Scheduling radiotherapy for patients with nasopharyngeal carcinoma in the corresponding time window can reduce radiation‐induced oral mucositis: A randomized, prospective study - Jun Lv; Shibin Liao; Bo Li; Linjiang Pan; Rensheng Wang (Cancer Medicine, 2023)
Abstract Background To explore a new method to reduce radiation‐induced oral mucositis by scheduling radiotherapy for patients with nasopharyngeal carcinoma (NPC) in the corresponding time window of the cycle of oral mucosal cells. Methods Eighty‐two NPC patients were randomly divided into a day group (n = 41) and a night group (n = 41). The radiotherapy was scheduled at noon (11:30–15:30) for the day group, while at night (19:00–23:00) for the night group. Oral mucositis and oral pain were recorded in both groups after each radiotherapy fraction. The short‐term efficacy of primary tumor regression, weight loss, and bone marrow suppression was recorded. Results The incidence of Grade 2 oral mucositis was 87.8% (36/41) and 63.4% (26/41) in the night group and day group, respectively (p = 0.010). The incidence of Grade 3 oral mucositis was 65.9% (27/41) and 22.0% (9/41) in the night group and day group, respectively (p < 0.001). The mean number of radiotherapy for patients to develop Grade 2 oral mucositis was 15.67 ± 5.05 and 20.92 ± 6.21 in the night group and day group, respectively. The incidence of Grade 2 oral pain was 48.8% (20/41) and 22.0% (9/41) in the night group and day group, respectively (p = 0.011). There were no significant differences in tumor regression, weight loss, and bone marrow suppression between the two groups. Conclusion By scheduling radiotherapy based on the corresponding time window of the cycle of oral mucosal cells, the severity of oral mucositis in NPC patients was reduced.